Esquema multifactorial de las anomalías del esmalte y sus efectos adversos en la salud oral - Karina Mercedes, Villarroel Cando (2021)
ABSTRACT This review literature was carried out with the aim of expanding knowledge on the etiology of dental enamel anomalies and their adverse effects on the health of the patient. The anomalies in the development of the enamel occur between the sixth and eighth week of intrauterine life, in this period there is a transformation of embryonic structures (dental sac, dental papilla and dental organ) that in the process of histodifferentiation form the enamel, dentin and cementum, which due to lack or increase in development produce anomalies of shape, number, size or structure and can occur due to an interaction between multiple factors. A literature search was carried out, extracted from databases such as Google Scholar, PubMed, Elsevier, Redalyc, Scielo, Science Direct, Scopus, through exclusion and inclusion criteria, also considering the average citation count (ACC) and the impact factor of the journal in which the article is published through Scimago Journal Ranking (SJR), were analyzed 60 publications. It was established that the etiology of the anomalies is of multiple nature as local factors (local hypoplasia), environmental factors (generalized hypoplasia), hereditary factors (amelogenesis imperfecta) these as the most present in the research field, these anomalies cause predisposition to caries, fractures, hypersensitivity, adhesion problems, excessive wear, causing adverse effects on oral health in addition to a decrease in the quality of life of the patient, Key words: Dental anomaly, hypoplasia, amelogenesis, Reviewed by: Danilo Yépez Oviedo English professor UNACH 0601574692